Gender differences in isolated upper-body poling among performance-matched cross-country skiers - Myhre, K.; Welde, B.; Hegge, A. M.; Sandbakk, O. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Although male and female elite skiers possess the same professionalism and general training patterns, it has recently been shown that gender differences increase as the contribution from poling increases. To gain further understanding about this phenomenon, the present study compared sprint and endurance performance, energetic capacities, efficiency during isolated upper-body poling, as well as body composition or training in male and female performance-matched cross-country skiers. Methods: Eight male cross country skiers (age 20±3 yrs, body mass 77.1±7.0 kg, VO2max 73.1±5.4 mL/min/kg, FIS 103±22) and nine female cross-country skiers (age 22±2 yrs, body mass 63.5±5.2 kg, VO2max 64.5±4.2 mL/min/kg, FIS 103±24) completed three 4-min submaximal stages, a 3-min performance test and a 30-sec Wingate sprint test on a modified Concept2 SkiErg. Ventilatory variables were assessed by open-circuit indirect calorimetry. Work rate and cycle rate were measured with the ergometers internal software, as validated with force and velocity measurements. Body composition was measured using dual-energy X-ray absorptiometry. Training data from the last six months before testing were quantified based on training diaries. Results: There were no differences in submaximal metabolic rate-work rate regressionlines between genders (all P<0.001). On the 3-min test, males achieved 95% higher work rate and 59% higher VO2peak (L/min) (both P<0.001). On the 30-sec test, males performed 114% higher work rate (P<0.001). Gender differences in work rate increased as intensity increased (P<0.05). Males had 35% and 59% higher absolute lean mass in trunk and arms (both P<0.001), and higher distribution of body mass localized in the upper body (61% vs 57%; P<0.001). Total training hours did not differ between genders, but males logged 113% more upper-body strength training and 35% more time in the classical technique than females (both P < 0.05). Conclusions: The differences in upper-body performance between men and women increased with increasing intensity, with the differences being significantly higher than what could be explained by diversity in aerobic energy delivery. The relationship between metabolic rate and work rate did not differ between genders, but the effect of intensity indicates that anaerobic capacity differentiates genders in upper-body exercise. This is further supported by the greater work per cycle and higher distribution of lean mass in the upper limbs among male skiers. Interestingly, training data indicated more upper-body strength and endurance training in males which might be an underlying reason for the relatively large differences in upper-body capacities.